2014
DOI: 10.1002/embj.201386082
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor-propagating cells and Yap/Taz activity contribute to lung tumor progression and metastasis

Abstract: Metastasis is the leading cause of morbidity for lung cancer patients. Here we demonstrate that murine tumor propagating cells (TPCs) with the markers Sca1 and CD24 are enriched for metastatic potential in orthotopic transplantation assays. CD24 knockdown decreased the metastatic potential of lung cancer cell lines resembling TPCs. In lung cancer patient data sets, metastatic spread and patient survival could be stratified with a murine lung TPC gene signature. The TPC signature was enriched for genes in the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
180
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(192 citation statements)
references
References 55 publications
11
180
0
1
Order By: Relevance
“…1f,g). TAZ, the YAP paralogue that shares many transcription factor targets with YAP, is previously shown to contribute to lung cancer progression and metastasis [22][23][24] . However, unlike YAP, TAZ expression showed no significant correlation with lung cancer pathologies ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1f,g). TAZ, the YAP paralogue that shares many transcription factor targets with YAP, is previously shown to contribute to lung cancer progression and metastasis [22][23][24] . However, unlike YAP, TAZ expression showed no significant correlation with lung cancer pathologies ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that miR-506 could suppress the proliferation of hepatoma cells through direct targeting of YAP mRNA in functional assays. YAP, an essential downstream effector of the Hippo pathway, is frequently highly expressed in a wide spectrum of human solid tumors [26,27] . It has been reported that YAP promotes proliferation in liver by regulating the transcription of certain target genes, including Ki-67, CTGF, c-Myc, sex-determining region Y-related high-mobility group box 4 (SOX4), H19, and alpha-fetoprotein (AFP) [19,20,28] .…”
Section: Discussionmentioning
confidence: 99%
“…The syntenic chromosomal region in mouse contains YAP gene that is amplified in mammary and liver tumors (Overholtzer et al, 2006;Zender et al, 2006). Ectopic expression or hyperactivation of YAP promotes cell growth and induces oncogenic transformation and epithelial-mesenchimal transition (EMT) that is often associated with metastasis (Lamar et al, 2012;Lau et al, 2014;Nallet-Staub et al, 2013;Overholtzer et al, 2006;Zhao et al, 2009;Zhao et al, 2008). In mouse, transgenic YAP overexpression or liverspecific knockout of Mst1/2 and Sav1 increases the number of stem/progenitor cells and determines liver overgrowth in a reversible manner, ultimately leading to hepatocellular carcinoma (HCC) (Camargo et al, 2007;Dong et al, 2007;Lee et al, 2010;Lu et al, 2010;Song et al, 2010;Zhou et al, 2009).…”
Section: Yap As An Oncogenementioning
confidence: 99%